2009
DOI: 10.1128/jcm.01062-09
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of Highly Diverse Variants of Cardiovirus , Cosavirus , Bocavirus , and Circovirus in Sewage Samples Collected in the United States

Abstract: Untreated sewage samples from 12 cities in the United States were screened for the presence of recently characterized RNA and DNA viruses found at high prevalence in the stool specimens of South Asian children. Genetic variants of human cosaviruses and cardioviruses in the Picornaviridae family and of DNA circoviruses and human bocaviruses were detected, expanding the known genetic diversity and geographic range of these newly identified viruses. All four virus groups were detected in sewage samples of less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 58 publications
4
100
0
Order By: Relevance
“…Interestingly, SCSDVs have been found to be abundant in reclaimed waters and sewage, suggesting that SCSDVs in the diseased corals examined here could be linked to environment degradation (Blinkova et al, 2009;Rosario et al, 2009). Previously it has been shown that environmental viruses such as human enteroviruses and adenoviruses are present on coral mucus, suggesting that these associations were the result of anthropogenic pollution (for example, runoff; Lipp et al, 2002Lipp et al, , 2007Futch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SCSDVs have been found to be abundant in reclaimed waters and sewage, suggesting that SCSDVs in the diseased corals examined here could be linked to environment degradation (Blinkova et al, 2009;Rosario et al, 2009). Previously it has been shown that environmental viruses such as human enteroviruses and adenoviruses are present on coral mucus, suggesting that these associations were the result of anthropogenic pollution (for example, runoff; Lipp et al, 2002Lipp et al, , 2007Futch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, there has been a surge in the number of novel picornaviruses discovered and genomes sequenced (4,13,14,15,17,23,33). In 2008, a novel picornavirus (porcine kobuvirus) was serendipitously identified by our laboratory from domestic pigs (25).…”
mentioning
confidence: 99%
“…Screening of waste waters for human viruses in multiple geographical areas has revealed the presence of newly described genera of the Picornaviridae family, i.e., Cosavirus, Cardiovirus, Salivirus, Kobuvirus (Alcala et al, 2010;Blinkova et al, 2009;Haramoto and Otagiri, 2013;Kitajima et al, 2014b;. More recent, deep-sequencing analysis of viral metagenomes from sewage and sewage sludge (also known as sewage viromes) has indicated that these novel human picornaviruses can be found in most cases at relatively higher abundance and occurrence than members of the Enterovirus genus (Aw et al, 2014;Bibby and Peccia, 2013;Cantalupo et al, 2011;Ng et al, 2012).…”
Section: Occurrence In Sewagementioning
confidence: 99%